Microstructure and method of manufacturing and using same

JP2024506034A5Inactive Publication Date: 2025-02-10DYNAMI BATTERY CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023547549
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-04
Filing Date
2022-02-03
Publication Date
2025-02-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing coating methods for articles with active materials result in homogeneous distributions, lacking control over the spatial arrangement of active and binding materials, leading to inefficient pathways for ion transport, catalytic reactions, and non-uniform release of active agents.

Method used

A method involving the self-assembly and self-separation of droplets containing active and binding materials to form microstructure units with non-uniform distributions, allowing precise control over the spatial arrangement of these materials.

Benefits of technology

Enhances ion transport, catalytic efficiency, and controlled release by creating optimized microstructures with reduced tortuosity and improved mechanical integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

1. A method for producing a structure, comprising the steps of obtaining a flowable liquid comprising a homogenous mixture of active material and binding material, generating a plurality of droplets from the flowable liquid, and depositing the generated plurality of droplets on a support, wherein the plurality of droplets self-assemble to form a continuous structure, the continuous structure comprising a plurality of microstructure units, and the active material and binding material self-segregate to form a non-uniform distribution of the active material and binding material in each unit.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The subject matter disclosed herein relates generally to microstructures and methods of making and using same. [Background technology]

[0002] Many manufactured articles or parts thereof are coated on a substrate with various active materials that are important to the particular function of the article. Current coating methods involve grinding the active materials, typically in particulate form, in a fluid with a binder material to produce a flowable liquid that can then be sprayed, blade cast, dip coated, screen printed, etc. onto the substrate. The role of the binder is to provide physical integrity to the coated structure and adhere it to the substrate. The coating step may also be followed by a drying step to remove the liquid. The resulting coating microstructure is typically on the micrometer scale.

[0003] Alternatively, the active material can be vaporized onto the substrate either physically at high temperatures or chemically in the form of reactive vapors. Such vapor-deposited coatings are typically on the nanometer scale.

[0004] All of these coating methods result in a homogenous coating microstructure with the active material evenly distributed throughout the coating.

[0005] Some applications, such as battery electrodes (e.g., anodes and / or cathodes), may have a metal foil, metallized polymer foil, or any other material capable of conducting electricity as a support onto which one or more layers of a composite material containing active materials and other elements are coated. The battery may be a primary or secondary battery of any current or future electrochemical type, such as a lithium-ion battery, having a structure of an anode electrode, a separator, and a cathode electrode. In such batteries, any type of electrolyte, liquid, gel, solid, etc., may be used as the electrolyte responsible for ion transport between the electrodes.

[0006] Existing techniques for electrode coating provide homogeneous distribution of active materials and elements, but do not provide micrometer or nanometer scale control over the spatial arrangement of particles of active materials, binders, and current enhancers. Conventional electrodes are made from active materials that are randomly sized, randomly oriented, and relatively poorly packed, creating long, indirect paths for lithium ions to travel through the electrolyte. In materials science, these paths are described as “tortuous.” As described in [1]Gene Berdichevsky, Gleb Yushin, “The Future of Energy Storage, Towards a Perfect Battery with Global Scale” (Sila Nanotechnologies, Inc., Sep. 2, 2020). 1], such tortuous paths are like a stadium with no rows of seats, just randomly distributed seats. In addition, conventional electrodes use an excessive amount of inactive materials, both polymer binders and conductive additives, because it is difficult to distribute those inactive materials only where they are needed in the electrode (at the points where the particles contact each other).

[0007] As another example, in catalytic reactions, it may be advantageous to have active catalytic materials located at or near the surface of the coating to facilitate access for chemical reactants to the catalytically active sites and to facilitate transport away of products of the chemical reaction after the chemical reaction is completed.

[0008] In homogeneous catalytic coatings, active catalytic sites located deep within the coating structure have poor access to chemical reactants and the products of the chemical reaction take time to be transported, so even a uniform distribution of catalytic active sites does not necessarily provide an optimal structure for catalytic reactions.

[0009] Yet another example is controlled release applications, where it is desired to release a compound or drug in a controlled manner in a transport medium such as body fluid. In a homogeneous coating of an active agent on a support, the active agent located at or near the surface of the coating will be released faster than the active agent buried deep within the microstructure of the coating, leading to non-uniform release of the active agent. In this example of controlled release, it may be considered more desirable to purposefully place the active agent deep within the microstructure of the coating, rather than at the surface, in order to release the active agent more uniformly. Summary of the Invention

[0010] Thus, there is a need to produce coating materials with defined microstructures that control the spatial distribution of active material within the microstructure to provide optimal functionality of the coating material and coated articles.

[0011] These and other aspects, objects, features, and advantages of the exemplary embodiments will become apparent to those of ordinary skill in the art upon consideration of the following detailed description of the exemplary embodiments.

[0012] In one aspect, the present disclosure provides a method of making a structure, the method comprising obtaining a flowable liquid comprising a homogenous mixture of active material and binding material, generating a plurality of droplets from the flowable liquid, and depositing the plurality of droplets on a support, the plurality of droplets self-assemble to form a continuous structure, the continuous structure comprising a plurality of microstructure units, the active material and binding material self-segregating to form a non-uniform distribution of the active material and binding material within each of the units.

[0013] In some embodiments, the active material imparts physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological, or a combination thereof, properties to the continuous structure. In some embodiments, the active material imparts electrical properties to the continuous structure, and the active material comprises one or more of a conductor, a semiconductor, or an insulator. In some embodiments, the active material is distributed within an area within each microstructure unit bounded by the respective unit. In some embodiments, the active material is distributed non-uniformly within the area of ​​each of the units.

[0014] In some embodiments, the binding material is an organic material, an inorganic material, or a combination thereof. In some embodiments, the binding material self-segregates and collects (or accumulates or accumulates) at the edges of the units. In some embodiments, the active material collects adjacent to the boundaries formed by the binding material. In some embodiments, the center of each unit is recessed and does not contain active material or binding material. In some embodiments, the binding material comprises a liquid carrier. In some embodiments, the liquid carrier comprises an inorganic composition or an organic composition.

[0015] In some embodiments, the method further comprises polymerizing the binding material, hi some embodiments, the polymerization is effected by heat or irradiation.

[0016] In some embodiments, the flowable liquid further comprises a substance adapted to alter the surface charge of at least one of the active materials or the binding material. In some embodiments, the substance adapted to alter the surface charge of at least one of the active materials or the binding material comprises a coupling agent. In some embodiments, the flowable liquid further comprises a substance adapted to alter the zeta potential of the active materials. In some embodiments, the substance adapted to alter the zeta potential of at least one of the active materials comprises a surfactant or dispersant.

[0017] In some embodiments, the droplets produced have an average volume ranging from 0.1 picoliters to 3000 picoliters. In some embodiments, the units have an average diameter ranging from 0.04 micrometers to 2000 micrometers. In some embodiments, the support comprises a metal film, a metallized plastic film, a metallized polymer film, a glass film, a ceramic film, a polymer film, or paper.

[0018] In some embodiments, the method further comprises controlling the size of the droplets. In some embodiments, controlling the size of the droplets comprises applying a force to the flowable liquid. In some embodiments, the force comprises mechanical pressure, collision with another liquid or fluid, ultrasound, electric charge, or a combination thereof. In some embodiments, controlling the size of the droplets comprises forcing the flowable homogenous liquid through orifices or openings of different sizes. In some embodiments, the method further comprises controlling at least one of the volume or position of the droplets with a digital control tool. In some embodiments, the flowable liquid has a viscosity of between 3 centipoise and 1500 centipoise.

[0019] In some embodiments, the continuous structure comprises a layer including a plurality of units along a plane of the support. In some embodiments, the continuous structure comprises a plurality of stacked layers along a plane of the support, each stacked layer including a plurality of units. In some embodiments, an average diameter of the units in a first layer of the plurality of stacked layers is different from an average diameter of the microstructure units in a second layer of the plurality of stacked layers. In some embodiments, the first layer of the plurality of stacked layers includes one or more of the following: a material different from one or more materials in a second layer of the plurality of stacked layers, or an active material the same as an active material in the second layer of the plurality of stacked layers, where the active material in the first layer has different physical, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological, or combinations thereof, properties than the same active material in the second layer of the plurality of stacked layers.

[0020] In some embodiments, each microstructural unit comprises an area bounded by at least three faces (or sides). In some embodiments, a subset of the plurality of microstructural units comprises an area bounded by six faces to form honeycomb cells. In some embodiments, the subset comprises a majority of the plurality of microstructural units. In some embodiments, each unit has a vertical aspect ratio of 1 or greater.

[0021] In some embodiments, the active material is a compound containing lithium. In some embodiments, the active material intercalates lithium ions or has a conversion reaction in the presence of lithium ions. In some embodiments, the support is included in the cathode (or positive electrode), anode (or negative electrode), separator, solid electrolyte, or semi-solid electrolyte.

[0022] In some embodiments, the active material is an active catalyst capable of effecting or facilitating a chemical reaction between reactants, and the reactants and products of the chemical reaction are transported through the microstructure unit. In some embodiments, the active material is an active adsorbent capable of selectively binding to an adsorbate, and a medium carrying the adsorbate is transported through the microstructure unit. In some embodiments, the active adsorbent provides a response upon binding to the adsorbate, and the response includes a change in at least one of the physical, chemical, electrical, optical, or magnetic properties of the active adsorbent. In some embodiments, the active material is an active carrier of a compound and is capable of releasing at least a portion of the compound in a controlled manner upon contact with a transport medium, and the transport medium is transported through the microstructure unit. In some embodiments, the active material is an active carrier of a photosensitive compound, and the photosensitive compound provides an optical response upon optical excitation. In some embodiments, the active material is an active carrier of a magnetically sensitive compound, and the magnetically sensitive compound provides a magnetic response upon magnetic excitation. In some embodiments, the active material is an active carrier for the pigment, providing an optical response when the pigment is excited with visible, ultraviolet, or infrared light. In some embodiments, the active material self-segregates and collects at the ends of the unit.

[0023] In another aspect, the present disclosure provides a structure comprising a plurality of microstructure units, where each unit comprises a binding material self-segregated from an active material forming a non-uniform distribution of binding material and active material in each unit. In some embodiments, the active material imparts physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological properties, or combinations thereof, to the structure. In some embodiments, the active material is distributed within the area of ​​each microstructure unit bounded by the respective unit. In some embodiments, the active material is non-uniformly distributed within the area of ​​each unit.

[0024] In some embodiments, the binding material comprises an organic material, an inorganic material, or a combination thereof. In some embodiments, the binding material self-segregates and collects at the edges of the units. In some embodiments, the active material collects adjacent to the boundaries formed by the binding material. In some embodiments, the center of each unit is recessed and does not contain active material or binding material. In some embodiments, the units have an average diameter of 0.04 micrometers to 2000 micrometers.

[0025] In some embodiments, the structure comprises a continuous planar layer. In some embodiments, the structure comprises a plurality of stacked planar layers. In some embodiments, a first layer comprises an active material that is the same as an active material of a second layer of the plurality of stacked layers, and the first layer has a different grain size characteristic than the second layer of the plurality of stacked layers.

[0026] In some embodiments, each microstructure unit comprises an area bounded by at least three sides. In some embodiments, a subset of the plurality of microstructure units comprises an area bounded by six sides to form honeycomb cells. In some embodiments, the subset comprises a majority of the plurality of microstructure units. In some embodiments, each unit has a vertical aspect ratio of 1 or greater.

[0027] In some embodiments, the active material intercalates lithium ions or has a conversion reaction in the presence of lithium ions. In some embodiments, the active material is an active catalyst capable of effecting or promoting a chemical reaction between reactants, and the reactants and products of the chemical reaction are passed through the microstructure unit. In some embodiments, the active material is an active adsorbent capable of selectively binding to an adsorbate, and a medium carrying the adsorbate is passed through the microstructure unit. In some embodiments, the active adsorbent provides a response upon binding to the adsorbent, the response including changes in physical, chemical, electrical, optical and magnetic properties of the active adsorbent. In some embodiments, the active material is an active carrier of a compound and is capable of releasing at least a portion of the compound in a controlled manner upon contact with a transport medium, and the transport medium is passed through the microstructure unit. In some embodiments, the active material is an active carrier of a photosensitive compound, and the photosensitive compound provides an optical response upon optical excitation. In some embodiments, the active material is an active carrier of a magnetically sensitive compound, and the magnetically sensitive compound provides a magnetic response upon magnetic excitation. In some embodiments, the active material is an active carrier for the pigment, providing the pigment with an optical response when excited with visible, ultraviolet, or infrared light.

[0028] In another aspect, the present disclosure provides an article of manufacture comprising any one or combination of structures described herein. In some embodiments, the article further comprises a substrate coated with the structure. In some embodiments, the substrate comprises a metal film, a metallized plastic film, a metallized polymer film, a glass film, a ceramic film, a polymer film, or paper.

[0029] In some embodiments, the article is an electrochemical cell. In some embodiments, the electrochemical cell includes an electrode that includes a structure. In some embodiments, the structure includes a conductive material. In some embodiments, the support is included in a cathode, an anode, a separator, a solid electrolyte, or a semi-solid electrolyte.

[0030] In another aspect, the present disclosure provides a composition comprising a flowable liquid comprising a homogenous mixture of an active material and a binding material, where when droplets of the composition are deposited on a substrate, the droplets self-assemble to form a continuous structure, the continuous structure comprising a plurality of microstructural units, and the binding material and active material self-segregate to form a non-uniform distribution of material in each of the units.

[0031] In some embodiments, the active material imparts physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological properties, or combinations thereof, to the continuous structure. In some embodiments, the binding material comprises an organic material, an inorganic material, or combinations thereof. In some embodiments, the binding material self-segregates to collect at the ends of the units.

[0032] In some embodiments, the binding material comprises a liquid carrier, hi some embodiments, the liquid carrier comprises an organic composition, an inorganic composition, or a combination thereof.

[0033] In some embodiments, the flowable liquid further comprises a substance adapted to change the surface charge of at least one of the active material or the binding material. In some embodiments, the substance adapted to change the surface charge of at least one of the active material or the binding material comprises a coupling agent. In some embodiments, the flowable liquid further comprises a substance adapted to change the zeta potential of the active material. In some embodiments, the substance adapted to change the zeta potential of the active material comprises at least one of a surfactant or a dispersant. In some embodiments, the mass ratio between the active material and the binding material is 0.000001 to 1,000,000. In some embodiments, the flowable liquid has a viscosity of 3 centipoise to 1,500 centipoise.

[0034] In another aspect, the present disclosure provides a method of manufacturing a structure, the method comprising obtaining a flowable liquid comprising a homogenous binding material, generating a plurality of droplets from the flowable liquid, and depositing the generated plurality of droplets onto a support, the plurality of droplets self-assemble to form a continuous structure, the continuous structure comprising a plurality of microstructure units, and the binding material self-segregates to form a non-uniform distribution of the binding material in each of the units.

[0035] In another aspect, the present disclosure provides a structure comprising a plurality of microstructure units, each of the units comprising a binding substance that is self-segregated to form a non-uniform distribution of the binding substance in each of the units. In another aspect, the present disclosure provides an article of manufacture comprising the structure. In some embodiments, the article further comprises a substrate coated by the structure. In some embodiments, the substrate comprises a polymer film. [Brief description of the drawings]

[0036] The accompanying drawings, which are included to provide a further understanding of embodiments of the invention, and which are incorporated in and constitute a part of this specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of embodiments of the invention.

[0037] [Figure 1] FIG. 1 illustrates a process for manufacturing a structure according to some embodiments.

[0038] [Diagram 2] FIG. 2A shows a droplet 203 containing a homogeneous liquid including active materials 207a and 207b and a binding material 209, according to some embodiments.

[0039] FIG. 2B illustrates the self-segregation of active materials 207a and 207b and binding material 209 to form a non-uniform distribution of active material and binding material in microstructure unit 205, according to some embodiments.

[0040] [Diagram 3] FIG. 3 illustrates the self-assembly and self-separation of droplets 303a-n to form structures 330 according to some embodiments.

[0041] [Figure 4] 4A-4C show cross sections of microstructure units 405a-c according to some embodiments.

[0042] [Diagram 5] FIG. 5 shows multiple layers 550a-n of a structure 530, according to some embodiments.

[0043] [Figure 6] FIG. 6 is a topographical optical image of a structure according to some embodiments.

[0044] [Figure 7] FIG. 7 is a topographical scanning electron microscope image of a structure according to some embodiments.

[0045] [Figure 8] FIG. 8A is a topographical scanning electron microscope image of a prior art commercially available electrode.

[0046] FIG. 8B shows an energy dispersive spectroscopy observation of the prior art commercial electrode shown in FIG. 8A.

[0047] [Figure 9] FIG. 9A is a topographical scanning electron microscope image of a structure according to some embodiments.

[0048] FIG. 9B illustrates a fluorine channel for energy dispersive spectroscopy of the structure shown in FIG. 9A, according to some embodiments.

[0049] [Figure 10] FIG. 10A shows a topographical scanning electron microscope image of a structure according to some embodiments.

[0050] FIG. 10B shows an energy dispersive spectroscopy view of the structure shown in FIG. 10A, according to some embodiments.

[0051] [Figure 11] FIG. 11 is a schematic diagram of the structure shown in FIGS. 10A-10B.

[0052] [Figure 12] FIG. 12 shows a structure with binding material but no active material according to some embodiments.

[0053] [Figure 13] FIG. 13 is a chart comparing structures produced by two different drying processes, according to some embodiments.

[0054] [Figure 14] FIG. 14 is a method of manufacturing a structure according to some embodiments.

[0055] [Figure 15] FIG. 15 is a method of manufacturing a structure according to some embodiments.

[0056] The figures described herein are for illustrative purposes and are not necessarily drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0057] The present disclosure provides structures having microstructural units whose properties can be controlled during the manufacturing process. The manufacturing process can include preparing a liquid including an active material and a binder material that can be ejected as droplets onto a support, where such droplets can self-assemble to form microstructural units in a continuous coating. Additionally, the binder material may self-separate from the active material such that the active material and / or binder material are non-uniformly distributed in each of the microstructural units. The present disclosure further provides methods of manufacturing structures in which the non-uniform distribution of the active material and / or binder material can be controlled to form microstructural units with desired properties.

[0058] In some embodiments, the self-assembly and self-segregation of active and binding materials can give rise to a number of phenomena. The self-assembly of droplets containing active and binding materials can form unique microstructural units during continuous coating. Depending on the battery application, the active materials can include lithium intercalation materials, conversion materials, or other charge transport species to form the cathode and / or anode electrodes. The self-segregation of binding materials that cannot participate in ion diffusion can significantly reduce the tortuosity of the conductive pathway, thereby forming an additional "secondary pore network" to facilitate ionic material transport. This secondary pore network can have the effect of improving the power density and charge rate of the battery without compromising the energy density of the electrode. The self-segregation of binding materials to or near the ends of the microstructural units can add structural strength to the microstructural units, thereby enhancing the mechanical integrity of the electrode. The self-segregation of active materials can also increase the interparticle contact of the active materials, improving the conductivity of the electrode.

[0059] In some embodiments, the structures may be coated onto an electrode of a battery, and the microstructured physical properties of the electrode coating may provide a higher power density compared to an electrode coated with the same material but without the microstructures.

[0060] The application of the method and structure provided herein is not limited to batteries.For example, the method and structure can be used in catalytic applications, medicines, aerospace technology, medical devices, consumer goods, etc.For example, in catalytic applications, active catalytic materials can be intentionally placed near the surface of the microstructure unit, allowing chemical reactants to easily access the active catalytic sites, while allowing the products of chemical reactions to be quickly transported away from the active catalytic sites.

[0061] In one aspect, the present disclosure provides a method of making the structures described herein. In general, the method may include obtaining a flowable liquid including an active material and a binding material (e.g., a homogenous mixture of active material and binding material), generating a plurality of droplets from the flowable liquid, and depositing the plurality of droplets generated from the flowable liquid onto a support. Upon deposition onto the support, the plurality of droplets may self-assemble to form a continuous structure including a plurality of microstructure units, and the active material and binding material may self-segregate to form a non-uniform distribution of material within each of the units.

[0062] FIG. 1 illustrates a process for fabricating a structure, according to some embodiments. In this example, a nozzle 101 may be used to generate and dispense multiple droplets 103 of a composition for fabricating a structure. The nozzle 101 may be controlled to move along the x, y, and / or z directions to deposit the droplets 103 at desired locations on a substrate. FIG. 1 illustrates the process occurring over time, including time intervals t1-t4, as described in more detail below in connection with FIG. 3.

[0063] In some embodiments, a composition for producing a structure may include a flowable liquid that includes an active material and a binder material. For example, the flowable liquid may include a homogenous mixture of the active material and the binder material.

[0064] In some embodiments, the flowable liquid may include a liquid carrier. For example, the binding material may include a liquid carrier. When the composition is deposited on the support, the liquid carrier may be evaporated to facilitate the construction of the structure. In some examples, the liquid carrier may include an organic composition. For example, the liquid carrier may be an organic solvent, such as N-methylpyrrolidone. In some examples, the liquid carrier may include an inorganic composition. In some examples, the liquid carrier may include a mixture or combination of an organic composition and an inorganic composition.

[0065] In some embodiments, the flowable liquid may include a material adapted to change the surface charge of the active material and / or the binding material. In some examples, the material may be adapted to change the surface charge of the active material. In some examples, the material may be adapted to change the surface charge of the binding material. In some examples, the material may include a coupling agent (e.g., an agent capable of enhancing adhesion or bonding between two materials). For example, the coupling agent may be a silane (e.g., a binary silicon-hydrogen compound and a compound having four substituents on silicon, including an organosilicon compound). Examples of silanes include trichlorosilane (SiHCl3), tetramethylsilane (Si(CH3)4), tetraethoxysilane (Si(OC2H5)4), and the like.)

[0066] In some embodiments, the flowable liquid may include a substance adapted to change the zeta potential of the active material. In some examples, such a substance may include a surfactant (e.g., a substance or compound that includes a hydrophobic tail and a hydrophilic head). Examples of surfactants include sodium stearate, 4-(5-dodecyl)benzenesulfonate, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), (2,4,4-trimethylpentan-2-yl)phenoxy]ethanol, octylphenol ethoxylate, and hexadecyltrimethylammonium bromide (CTAB). In some examples, such a substance may include a dispersant (e.g., a substance or compound that, when added to a suspension of particles, can improve separation of the particles and prevent settling or agglomeration of the particles). Examples of dispersants include sodium pyrophosphate, ammonium citrate, sodium citrate, sodium tartrate, sodium succinate, glyceryl trioleate, phosphate esters, random copolymers, comb polymers, poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA), ammonium polyacrylate, sodium polyacrylate, sodium polysulfonate, and poly(ethyleneimine). In some examples, dispersants may act sterically as well as change the zeta potential. Surfactants can disperse and change / adjust the surface tension.

[0067] In some embodiments, in the flowable liquid, the mass ratio between the active material and the binder material is from 0.000001 to 1000000, for example, from 0.000001 to 0.000005, from 0.000005 to 0.00001, from 0.00001 to 0.00005, from 0.00005 to 0.0001, from 0.0001 to 0.0005, from 0.0005 to 0.001, from 0.001 to 0.005, from 0.0005 to 0.001, from 0.001 to 0.005, from 0.0005 to 0.001, from 0.001 to 0.005, from 0.0005 to 0.0001, from 0.0005 ... It may be .005-0.01, 0.01-0.05, 0.05-0.1, 0.1-0.5, 0.5-1, 1-5, 5-10, 10-50, 50-100, 100-500, 500-1000, 1000-5000, 5000-10000, 10000-50000, 50000-100000, 100000-500000, or 500000-1000000.

[0068] In some embodiments, the flowable liquid may have a viscosity of 1 to 2000 centipoise, e.g., 3 to 1500, 3 to 50, 50 to 100, 100 to 200, 200 to 300, 300 to 400, 400 to 500, 500 to 600, 600 to 700, 700 to 800, 800 to 900, 900 to 1000, 1000 to 1100, 1100 to 1200, 1200 to 1300, 1300 to 1400, or 1400 to 1500 centipoise.

[0069] In some embodiments, nozzle 101 of FIG. 1 generates and dispenses droplets 103 that include a homogenous mixture of one or more active materials and binder materials. As described in more detail below in connection with FIGs. 2-3, each droplet 103 may self-assemble such that the active materials and binder materials self-segregate to form a continuous structure having multiple units 105a, 105b that form a non-uniform distribution of active materials and binder materials in each unit. The units may be in the form of honeycomb cells as shown by unit 105b, and in other embodiments, the units may have few ends (or no ends) as shown by unit 105a.

[0070] The resulting droplets 103 may have a volume suitable for fabricating structures. In some embodiments, the droplets generated may have an average volume of 0.1 picoliters to 5000 picoliters, e.g., 0.1 to 3000, 0.1 to 100, 100 to 250, 250 to 500, 500 to 750, 750 to 1000, 1000 to 1250, 1250 to 1500, 1750 to 2000, 2000 to 2250, 2250 to 2500, 2500 to 2750, 2750 to 3000, 1 to 100, 1 to 80, 1 to 60, 1 to 50, 2 to 50, 3 to 50, 3 to 10, 5 to 15, 10 to 20, 15 to 25, 20 to 30, 25 to 35, 30 to 40, 35 to 45, or 40 to 50 picoliters. In some examples, the droplets formed may have an average volume between 0.1 and 3000 picoliters.In some examples, the droplets formed may have an average volume between 3 and 50 picoliters.

[0071] The method may further include controlling the size of the generated droplets 103. In some embodiments, the size of the droplets may be controlled by applying a force to the flowable liquid. For example, the force may be mechanical pressure, collision with another liquid or fluid, ultrasound, electric charge, or a combination thereof. In some examples, the size of the droplets may be controlled by forcing the flowable homogenous liquid through orifices or openings of different sizes.

[0072] In some embodiments, the volume of the droplets may be controlled by a digitally controlled tool. During the manufacturing process, the position of the droplets deposited on the surface may be similarly controlled by a digitally controlled tool. In some examples, the droplets may be generated and deposited by a printing technique (e.g., a 3D printing technique, a drop-on-demand industrial inkjet printing technique, a digital printing technique, or a computer-controlled inkjet printing technique), a digital manufacturing technique, or a digital deposition technique. Examples of printing techniques are described in Hebner, TR et al., (1998) Appl. Phys. Lett., 72, 519-521 (1998), Blazdell, PF et al., Mater. Process. Technol., 99, 94-102 (2000), Jacobs, HO, Science, 291, 1763-1766 (2001), Zhao, Y et al., Electrochim. Acta, 51, 2639-2645 (2006), and Xu, F et al., Chem. Phys. Lett., 375, 247-251 (2003), which are incorporated herein by reference in their entireties. In some examples, the methods and compositions described herein allow for control of the synthesis of electrodes at the microscale level, resulting in 3D structures that improve battery performance.

[0073] Although not shown in Figure 1, in some embodiments, the method may further include polymerizing the binding material. For example, the binding material may be polymerized by heat or irradiation. In some examples, polymerization may occur after the binding material and active material have self-segregated to fix the location or distribution pattern of the binding material and / or active material.

[0074] 2A illustrates a droplet including a homogenous liquid including an active material and a binder material, according to some embodiments. In some embodiments, the resulting droplet 203 may include multiple active materials and / or multiple binder materials. In the example illustrated in FIG. 2A, the droplet 203 includes a first active material 207a, a second active material 207b, and a binder material 209, which are uniformly distributed throughout the droplet 203.

[0075] FIG 2B shows that the active material and binder material self-segregate to form a non-uniform distribution of the active material and binder material in the microstructure unit according to some embodiments. FIG 2B shows that after the droplet 203 is deposited on the support, the active material 207a-b and binder material 209 self-segregate to form a non-uniform distribution of the active material and binder material in the microstructure unit 205 formed by the droplet. As shown in FIG 2B, the binder material 209 self-segregates from the active material and mainly collects at the ends (or edges, or edges) of the microstructure unit 205.

[0076] In some embodiments, the structure includes a plurality of microstructure units 205. The structure may include an active material and a binding material. The active material and binding material may self-segregate when deposited on a surface or support in forming the structure. When separated from the active material, the binding material may collect in a particular area of ​​the unit. Similarly, when separated from the binding material, the active material may collect in a particular area of ​​the unit, which may be the same or different than the area where the binding material collects. Such self-segregation of the active material and the binding material may result in (or cause) a non-uniform distribution of the materials in the structure, which results in the formation of a microstructure including a plurality of units. The non-uniform distribution may be controlled by the manufacturing process so that the microstructure units have desired properties, such as desired physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, or biological properties, or any combination thereof. Each of the microstructure units may include an active material and a binding material. In some embodiments, each of the units may include one or more active materials and / or one or more binding materials.

[0077] FIG. 3 illustrates the self-assembly and self-separation of liquid droplets to form a structure, according to some embodiments. FIG. 3 illustrates an example of the self-assembly of droplets 303a-n occurring over time, beginning at time t1 and ending at time t4. In FIG. 3, droplets 303a-n include a first active material 307a, a second active material 307b, and a binder material 309. However, in other embodiments, there may be only one active material and / or binder material. In this example, droplets 303a-n are shown immediately after deposition on a support or surface, as described above in connection with FIG. 1, at t1. As shown at times t2 and t3, droplets 303a-n begin to self-assemble to form a continuous structure. The self-assembly process may be induced by the manipulation of capillary flow and evaporation of droplets 303a-n. Further, at times t2, t3, active materials and binder materials self-assemble in each of the droplets, as described above in connection with FIG. 2A-B. The process of self-assembly continues from t1 to t4, forming a continuous structure comprising microstructural units 305a-n, each microstructural unit comprising a non-uniform distribution of active material and binding material.

[0078] Self-assembly of droplets can be driven by a reduction in surface energy. Droplets may tend to coalesce and self-assemble into the form with the lowest surface energy. Self-segregation in mixtures of materials can be driven by surface charge properties. If the surface charges are similar, Coulombic repulsion may dominate, leading to self-segregation. On the other hand, if the surface charges are different, Coulombic attraction may dominate, leading to self-aggregation. Methods for changing the surface charge properties of materials include introducing surfactants to enhance steric hindrance or adding coupling agents such as silanes.

[0079] In some instances, the self-segregated binding material may collect at the ends of the units. The active material may be distributed within the regions within each microstructure unit bounded by the respective units. In some instances, the active material may be distributed non-uniformly within the regions of each unit.

[0080] 4A-4C show cross-sections of microstructure units according to some embodiments. In all of the microstructure units 405a-c in FIG. 4A-4C, the active materials 407a-b are concentrated at the center of the unit, and the binding material 409 is concentrated at the center of the unit. In all of the microstructure units 405a-c in FIG. 4A-4C, the active materials 407a-b are accumulated at the center of the unit, and the binding material 409 is accumulated at the edge of the unit. The edge of the microstructure unit may be higher (e.g., FIG. 4A), uniform (e.g., FIG. 4B), or lower (e.g., FIG. 4C) than the center of the unit.

[0081] The microstructural units may be three-dimensional open-ended cells. In some embodiments, some or all of the microstructural units may include an area bounded by at least three sides, e.g., 3, 4, 5, 6, 7, 8, 9, 10 or more sides. In some examples, the lengths of the sides may be substantially the same. In one example, a subset or all of the microstructural units (e.g., a majority of the microstructural units in the structure, e.g., at least 50%, 60%, 70%, 80%, 90%, 95%, or 99%) may include an area bounded by six sides. Such units may be bounded by six sides having substantially the same length, e.g., in the shape of a honeycomb cell.

[0082] In some embodiments, the units are 0.01 to 3000 micrometers, e.g., 0.02 to 2000, 0.04 to 2000, 0.04 to 1500, 0.04 to 1000, 0.04 to 500, 1 to 500, 5 to 500, 10 to 500, 20 to 500, 25 to 500, 25 to 100, 40 to 80, 50 to 70, 45 to 55, 50 to 60, 55 to 65, 60 to 70, 65 The units may have an average diameter of 50 to 75, 70 to 80, 25 to 50, 50 to 100, 100 to 150, 150 to 200, 200 to 250, 250 to 300, 300 to 350, 350 to 400, 400 to 450, or 450 to 500, 500 to 750, 750 to 1000, 1000 to 1250, 1250 to 1500, 1500 to 1750, or 1750 to 200 micrometers. In one example, the units may have an average diameter of 50 to 70 micrometers, such as 50 to 55, 55 to 60, 60 to 65, or 65 to 70 micrometers.

[0083] In some embodiments, each microstructure of a unit in the structure can have a vertical aspect ratio (e.g., the ratio of thickness to diameter of the unit) equal to 1 or greater, e.g., 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.5, 4, 4.5, or 5.

[0084] In some embodiments, the structure may be a continuous structure. The structure may include a continuous layer (e.g., a continuous planar layer). The layer may be along a planar surface of a support. In some embodiments, the structure may include multiple stacked layers (e.g., stacked planar layers).

[0085] Figure 5 is a diagram illustrating multiple layers of a structure, according to some embodiments. Figure 5 shows a structure 530 having multiple layers 550a-n. Each layer 550 includes a microstructural unit including a first active material 507a, a second active material 507b, and a binder material 509.

[0086] In some embodiments, the structure may include at least 2, 5, 10, 50, 100, 150, 200, 250, 300, 350 stacked layers (e.g., stacked planar layers). In some examples, a first layer of the stacked layers may include the same active material as the active material of a second layer of the stacked layers, and the first layer has a different particle size characteristic than the second layer of the plurality of stacked layers. In some examples, the average diameter of the units of the at least two layers may be different. In some examples, the average diameter of the units of the at least two layers may be the same. In some examples, a first layer of the plurality of stacked layers may include the same active material with a different material or materials in a second layer of the plurality of stacked layers, or different physical, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological, or combination thereof properties in the second layer of the plurality of stacked layers.

[0087] The active material is not particularly limited as long as it is a material that provides a function. The active material may provide the function of the structure. For example, the active material may impart a physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological property, or a combination thereof to the structure. In one example, the active material may impart a physical property (e.g., material density, porosity, strength, shape, etc.) to the structure. In another example, the active material may impart a thermal property to the structure. In another example, the active material may impart a chemical property to the structure. In another example, the active material may impart a catalytic property to the structure. In another example, the active material may impart an electrical property to the structure. In another example, the active material may impart a magnetic property to the structure. In another example, the active material may impart a radioactive property to the structure. In another example, the active material may impart an optical property to the structure. In another example, the active material may impart a biological property to the structure.

[0088] In some embodiments, the active material may intercalate ions (e.g., lithium ions) or have a conversion reaction in the presence of ions (e.g., lithium ions). For example, the active material may promote a chemical reaction in which ions (e.g., lithium ions) are inserted into a host matrix while essentially retaining the crystal structure. In some embodiments, the active material may include transition metals (e.g., nickel, cobalt, manganese, copper, zinc, vanadium, chromium, iron) and their oxides, phosphates, phosphites, sulfides, and silicates, as well as alkali and alkaline earth metals, aluminum, aluminum oxide, and aluminum phosphate. Examples of active materials include LiCoO2, LiMn2O4, LiFePO4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiC6, Li4Ti5O 12 , LiNiCoAlO2, LiNiCoMnO2, LiNi 0.5 Mn 1.5 O4, Li2TiO3, Li(Ni 0.5 Mn 0.5 )O2, Li2S, graphite (man-made or natural), hard carbon, titanates, titania, transition metals in general, halides, and / or chalcogenides, silicon, and other elements of group 14 (e.g., tin, germanium, etc.). In some examples, the active material may include LiFePO4. In some embodiments, the active material may be an insulator.

[0089] In some embodiments, the active material may be an active catalyst capable of effecting or facilitating a chemical reaction between reactants, and the reactants and / or products of the chemical reaction may be transported through the microstructure unit. In some examples, the catalyst may be an enzyme or a chemical catalyst.

[0090] In some embodiments, the active material may be an active adsorbent that can selectively bind to the adsorbate, and a medium carrying the adsorbate may be transported through the microstructure unit. The active adsorbent may be a material (e.g., a solid or semi-solid material) that can bind (e.g., selectively bind) to the adsorbate, and the adsorbate may be a gas, or a dissolved or suspended particle in a solution, or a mixture thereof. In some embodiments, the active adsorbent may provide a response upon binding to the adsorbate. Such a response may be a change in the physical, chemical, electrical, optical, magnetic properties of the adsorbent, or any combination thereof. In some examples, such a response may be a measurable response, e.g., light, sound, electrical signal.

[0091] In some embodiments, the active material may be an active carrier of a compound, and at least a portion of the compound may be released in a controlled manner upon contact with a transport medium, which may be transported through the microstructure unit. For example, the transport medium may transport the compound through the microstructure unit. The transport medium may be in a gas, liquid, or solid state. In one example, the transport medium may be a bodily fluid (e.g., blood, urine, saliva).

[0092] In some embodiments, the active material may be an active carrier of a photosensitive compound, which may provide an optical response upon photoexcitation. Examples of photosensitive compounds include fluorescent dyes.

[0093] In some embodiments, the active material may be an active carrier for a magnetically susceptible compound. The magnetically susceptible compound may provide a magnetic response when magnetically excited. In some embodiments, the active material may be an active carrier for a pigment. The pigment may have an optical response (e.g., produce an optical signal) when excited (e.g., with visible, ultraviolet, or infrared light).

[0094] The binding material may be any material that can promote the adhesion of particles in the active material in the structure. In some examples, the binding material may include an organic material. In some examples, the binding material may include an inorganic material. In some examples, the binding material may include a combination or mixture of organic and inorganic materials. In one example, the binding material may be a polymer, such as polyvinylidene fluoride (PVdF), carboxyl methyl cellulose (CMC), styrene butadiene rubber (SBR), or a mixture or combination thereof.

[0095] The structure may include one or more additional components necessary for a particular function. In some embodiments, the structure may include one or more conductive materials. Examples of conductive materials include carbon (e.g., nanometer-sized carbon), such as carbon black, graphite, Ketjen black, graphitic carbon, low-dimensional carbon (e.g., carbon nanotubes), and / or carbon fibers.

[0096] 6 is a topographical optical image of a structure according to some embodiments. FIG. 6 shows an optical photograph (taken with an optical microscope) of an exemplary structure including microstructural units, e.g., honeycomb-shaped microstructural units. The photograph shows a top view of the structure, such as the structure described above in connection with FIG. 5.

[0097] 7 is a topographical scanning electron micrograph image of a structure according to some embodiments. The structure shown in FIG. 7 is a structure coated on a lithium ion cathode including multiple microstructure units with non-uniform distribution of active material and binding material. In each of the microstructure units, the active material and binding material self-segregated to form a non-uniform distribution with the binding material clumping along the edge of the unit. As shown in FIG. 7, in the microstructure units, there is about 40% more binding material at the edge of the unit than in the center of the unit.

[0098] The structure of FIG. 7 may be manufactured with a composition including the components in Table 1 below, and the structure may include LiFePO4 (active material), Triton-X100, carbon black, and PVdF Solef 5130 (binding material).

[0099] In some examples, the flowable liquid may include the components in Table 1 below. [Table 1]

[0100] For comparison, Figures 8A and 8B are photographs of the material distribution of a commercial electrode made by prior art techniques such as blade casting, die casting, tape casting, or slot die coating techniques. Figure 8A is a topographical scanning electron micrograph image of the commercial electrode. Figure 8B shows an energy dispersive spectroscopy observation of the commercial electrode taken using a scanning electron microscope (SEM). As shown in 8A-8B, there is a homogenous and uniform distribution of binding material and active material, which differs from the non-uniform distribution of material in structures according to the present disclosure, such as the structure shown in Figure 7.

[0101] FIG. 9A is a topographical scanning electron micrograph image of a structure according to some embodiments. FIG. 9B shows the fluorine channel of an energy dispersive spectroscopy observation of the structure shown in FIG. 9A according to some embodiments. Fluorine is only present in the PVDF binding material used in this sample. FIGs. 9A and 9B show another example of a structure where the binding material is collected at the edge of the microstructure unit. FIGs. 9A and 9B show the top layer of the electrode microstructure.

[0102] FIG. 10A shows a topographical scanning electron micrograph image of a structure according to some embodiments. FIG. 10B shows an energy dispersive spectroscopy observation of the structure shown in FIG. 10A according to some embodiments. FIGS. 10A and 10B show yet another example of a structure in which the binding material is concentrated at the edges of the microstructure units. In this structure, the active material is also concentrated at the edges, but within the boundaries formed by the binding material, e.g., the microstructure units are "dimpled" (referring to a higher density of material at the edges than in the center of the microstructure units). The light gray areas in FIG. 10B show the ionic nature of the active material.

[0103] FIG. 11 is a schematic diagram of the "dimple" structure of FIGS. 10A and 10B. 10A and 10B. In some examples, the structure 1130 may include conductive material distributed not only along the edges of the units but also within the boundaries formed by the binding material. In some examples, the "dimple" structure may have multiple layers 1150a-n of microstructure units, as shown in FIG. 11. The microstructure unit of FIG. 11 includes a first active material 1107a, a second active material 1107b, and a binding material 1109.

[0104] 12 is a schematic diagram of another example of a structure according to the present disclosure. The structure 1230 may include a binding material but may not include an active material. The binding material may be collected at the ends of the microstructure units. The structure 1230 may include one or more layers, for example, a plurality of layers 1205a-n.

[0105] The distribution of active material (e.g., within the microstructure units or at the edges of the microstructure units) can be controlled by the manufacturing process. In some embodiments, the distribution of active material can be controlled by modifying the drying process. For example, different types of infrared (IR) protocols can be used. FIG. 13 shows that different IR exposures result in different distributions of active material in the microstructure units. In the drying process, at lower IR exposure, the active material gathers at the edges of the resulting microstructure units (e.g., forming "dimpled" units), and at lower IR exposure, the active material gathers within the edges of the resulting microstructure units (e.g., forming "filled" units).

[0106] 14 shows a flow chart of a method 1400 of fabricating a structure according to some embodiments. Method 1400 includes steps 1402, 1404, and 1406. Step 1402 includes obtaining a flowable liquid including a homogenous mixture of active material and binder material. Step 1404 includes generating a plurality of droplets from the flowable liquid. Step 1406 includes depositing the plurality of droplets onto a support. In some embodiments, the continuous structure may include a plurality of microstructure units, where the active material and binder material self-segregate to form a non-uniform distribution of active material and binder material in each of the units.

[0107] 15 shows a flow chart of a method 1500 of fabricating a structure, according to some embodiments. The method 1400 includes steps 1502, 1504, and 1506. Step 1502 includes obtaining a flowable liquid including a homogenous binding material. Step 1504 includes generating a plurality of droplets from the flowable liquid. Step 1506 includes depositing the generated plurality of droplets onto a support. In some embodiments, the plurality of droplets may self-assemble to form a continuous structure, the continuous structure including a plurality of microstructure units, and the binding material self-segregates to form a non-uniform distribution of the binding material in each unit.

[0108] In another aspect, the present disclosure provides an article comprising the structure described herein. In some examples, the article may include a substrate coated with the structure. Such substrates may include a metal film, a metallized plastic film, a metallized polymer film, a glass film, a ceramic film, a polymer film, or a paper. In one example, the substrate may be a metal film. In another example, the substrate may be a metallized film. In another example, the substrate may be a plastic film. In another example, the substrate may be a glass film. In another example, the substrate may be a ceramic film. In another example, the substrate may be a polymer film. In another example, the substrate may be a paper. In some examples, the article may include a member filled with a material having the structure described herein.

[0109] In some embodiments, the article may be an electrochemical cell. The electrochemical cell may include one or more electrodes that include (e.g., are coated with) the structures. In some examples, the electrodes may include structures having microstructural units, e.g., honeycomb shaped, each bounded by six sides. The electrodes may include multiple layers of the structures. In some examples, at least two of the layers may be offset.

[0110] In some embodiments, this structure may be used to coat an electrode to improve battery performance. In some examples, an inkjet printed coffee stain droplet effect may be used to control the placement of active and binding materials on the substrate, thereby allowing precise control of the electrode microstructure. In some examples, the structure coating the electrode may have a honeycomb shaped microstructure, for example, where the binding material forms a honeycomb shape and the areas within the honeycomb units are filled with active material. Such structures may be layered in various ways to optimize the performance of the electrochemical cell depending on the application. In some examples, the electrode includes single or multiple layers of printed honeycomb structures.

[0111] The microstructural units in the structure on the electrode may have certain physical properties, such as material density, porosity, arrangement of binding materials, etc. In some embodiments, such properties may enhance the mass transport of ions (e.g., lithium ions) through the electrode, which may result in higher power density when compared to an electrode using the same material but without the microstructural units. In some embodiments, the structure may include a secondary pore network. Such a network may be capable of modifying ion transport within the microstructure, for example, increasing ion diffusion (e.g., lithium ion diffusion) through the electrode.

[0112] In some embodiments, structures having microstructural units may be stronger than amorphous structures, resulting in stronger battery electrodes with reduced or no electrode cracking. Since electrode cracking is one of the most important issues affecting battery life, electrodes having structures described herein may have longer battery cycle life when compared to electrodes of the same material but without microstructural features.

[0113] In some embodiments, multiple components of an electrochemical cell may include the structures described herein. For example, one or more cathodes, one or more anodes, one or more separators, one or more solid or semi-solid electrolytes, one or more other battery chemicals or electrical devices, or any combination thereof, may include the structure (e.g., be coated by the structure) for a desired function. For example, one or more cathodes, one or more anodes, one or more separators, one or more solid or semi-solid electrolytes, one or more other battery chemicals or electrical devices, or any combination thereof, may include the structure or may be used as a support in fabricating the structure.

[0114] As used herein, the singular forms "a," "an," and "the" include both the singular and plural referents unless the context clearly indicates otherwise.

[0115] The terms "optional" or "optionally" mean that the subsequently described event, circumstance, or substituent may or may not occur, and the description includes instances in which the event or circumstance occurs and instances in which it does not occur.

[0116] The recitation of numerical ranges by endpoints includes all numbers and fractions subsumed within each range, as well as the recited endpoints.

[0117] As used herein, the term "about" in connection with reference numerical values ​​and grammatical equivalents thereof, includes the numerical value itself and a range of values ​​from the numerical value plus or minus 10%. For example, the amount "about 10" includes 10 and any amount from 9 to 11.

[0118] The term "substantially the same" or "essentially the same" means that the similarity between two or more values, compositions, or properties is high enough that one of ordinary skill in the art would consider the difference between those values, compositions, or properties to be statistically marginal or insignificant within the context of the property being measured. The difference between two substantially the same values ​​is, for example, less than 10%.

[0119] The term "exemplary" as used herein means serving as an example, instance, or illustration. Any aspect or design described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other aspects or designs. Rather, use of the word exemplary is intended to present concepts in a concrete manner.

[0120] Various embodiments are described below. It should be noted that a particular embodiment is not intended as an exhaustive description or as a limitation to the broad aspects discussed herein. An aspect described in conjunction with a particular embodiment is not necessarily limited to that embodiment and can be practiced with any other embodiment(s). References throughout this specification to "one embodiment," "an embodiment," or "an example embodiment" mean that a particular feature, structure, or characteristic described in connection with an embodiment is included in at least one embodiment of the present invention. Thus, although the phrases "in one embodiment," "in one embodiment," or "an example embodiment" appear in various places throughout this specification, they do not necessarily all refer to the same embodiment, and may. Furthermore, particular features, structures, or characteristics can be combined in any suitable manner in one or more embodiments, as would be apparent to one of ordinary skill in the art from this disclosure. Furthermore, some embodiments described herein include some features but not other features included in other embodiments, but it is meant that combinations of features of different embodiments are within the scope of the present invention. For example, in the appended claims, any of the claimed embodiments can be used in any combination.

[0121] All publications, published patent documents, and patent applications cited in this specification are herein incorporated by reference to the same extent as if each individual publication, published patent document, or patent application was specifically and individually indicated to be incorporated by reference.

[0122] Various modifications and variations of the described methods, compositions, and kits of the present invention will be apparent to those skilled in the art without departing from the scope and spirit of the present invention. Although the present invention has been described in connection with specific embodiments, it will be understood that the invention is capable of further modifications, and that the invention as claimed should not be unduly limited to such specific embodiments. Indeed, various modifications of the described modes for carrying out the invention that are obvious to those skilled in the art are intended to be within the scope of the present invention. This application is generally intended to cover any variation, use, or adaptation of the present invention, including those in accordance with the principles of the present invention, where deviations from the present disclosure are within known customary practices in the art to which the invention pertains and may be applied to the essential features as previously defined herein.

Claims

1. Obtaining (1402) a flowable liquid comprising a homogenous mixture of active material (207, 307, 407, 507, 1107) and binding material (209, 309, 409, 509, 1109); generating (1404) a plurality of droplets (103, 203, 303) from the fluid liquid; and depositing (1406) the plurality of droplets formed on a support; the plurality of droplets self-assemble to form a continuous structure (330, 530, 1130); the continuous structure comprises a plurality of microstructure units (105, 205, 305, 405); and A method of manufacturing a structure (1400), wherein the active material and the binding material self-segregate to form a non-uniform distribution of the active material and the binding material in each unit.

2. the active material imparts physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological, or a combination thereof, properties to the continuous structure; and The method of claim 1 , wherein the active material imparts electrical properties to the continuous structure, the electrical properties including being an electronic conductor, an ionic conductor, a semiconductor, an electrical insulator, or a combination thereof.

3. 13. The method of any one or combination of the preceding claims, wherein the active material is non-uniformly distributed within the area of ​​each microstructure unit bounded by the respective unit.

4. 13. The method of any one or any combination of the above claims, wherein the binding material is an organic material, an inorganic material, or a combination thereof, or the binding material comprises a liquid carrier comprising an inorganic or organic composition.

5. A method according to any one or combination of the preceding claims, wherein the uneven distribution of the active material and the binding material in each of the units comprises one or more of the following: The binding material self-segregates and collects at the end of the unit. the binding material collects adjacent to a boundary formed by the binding material; Each unit has a hollow center and contains no active or binding material, or The active material self-segregates and collects at the ends of the unit.

6. 13. The method of any one or any combination of the preceding claims, further comprising polymerizing the binding material, wherein the polymerization is effected by heat, a catalyst, irradiation, or a combination thereof.

7. 13. The method of any one or any combination of the preceding claims, wherein the flowable liquid further comprises a substance adapted to alter the surface charge of at least one of the active material or the binding material, the substance comprising a coupling agent, a silane, a surfactant, a dispersant, or a combination thereof.

8. The droplets produced have an average volume ranging from 0.1 picoliters to 3000 picoliters; the units have an average diameter of from 0.04 micrometers to 2000 micrometers; or 10. The method according to any one or combination of the preceding claims, wherein the flowable liquid has a viscosity of between 3 centipoise and 1500 centipoise.

9. 20. The method of any one or any combination of the preceding claims, wherein the support comprises a metal film, a metallized plastic film, a metallized polymer film, a glass film, a ceramic film, a polymer film, or paper.

10. A method according to any one or any combination of the above claims, further comprising controlling at least one of the volume, size or position of the droplet by a digitally controlled tool.

11. 10. The method of any one or any combination of the preceding claims, wherein the continuous structure comprises a layer (550, 1150) or a plurality of stacked layers (550, 1150), each layer comprising a plurality of said units along the plane of the support.

12. The method described in claim 11, wherein the continuous structure includes a plurality of stack layers, and the average diameter of the units in a first layer of the plurality of stack layers is different from the average diameter of the microstructure units in a second layer of the plurality of stack layers.

13. The method of claim 11, wherein the continuous structure comprises a plurality of stacked layers, and a first layer of the plurality of stacked layers comprises one or more of the following: a material different from one or more materials in a second layer of the plurality of stacked layers; or an active material that is the same as an active material in the second layer of the plurality of stacked layers, wherein the active material in the first layer has different physical, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological, or combination thereof, properties than the same active material in the second layer of the plurality of stacked layers.

14. 11. The method of any one or any combination of the preceding claims, wherein each microstructural unit comprises an area bounded by at least three sides, and one or more of the plurality of microstructural units comprises an area bounded by six sides to form honeycomb cells.

15. 2. The method according to any one or any combination of the above claims, wherein the active material is a compound containing lithium, and the active material intercalates lithium ions or has a conversion reaction in the presence of lithium ions.

16. 20. The method of any one or any combination of the preceding claims, wherein the support is comprised in a cathode, an anode, a separator, a solid electrolyte, or a semi-solid electrolyte.

17. The method of any one or any combination of claims 1 to 14, wherein the active material comprises one or more of the following: an active catalyst capable of effecting or promoting a chemical reaction between reactants, said reactants and products of said chemical reaction being passed through said microstructure unit; an active adsorbent capable of selectively binding to an adsorbate, and a medium carrying the adsorbate is passed through the microstructure unit; an active adsorbent capable of providing a response upon binding to an adsorbate, said response comprising a change in at least one of a physical, chemical, electrical, optical or magnetic property of said active adsorbent; an active carrier of a compound and capable of releasing at least a portion of said compound in a controlled manner upon contact with a transport medium, said transport medium being passed through said microstructure unit; an active carrier for a photosensitive compound, the photosensitive compound providing an optical response when excited by light; an active carrier of a magnetically sensitive compound, said magnetically sensitive compound providing a magnetic response when magnetically excited; or It is an active carrier for a pigment, which provides an optical response when the pigment is excited with visible, ultraviolet, or infrared light.

18. A structure (330, 530, 1130) comprising a plurality of microstructure units (105, 205, 305, 405), each of said units comprising a binding material (209, 309, 409, 509, 1109) self-segregated from an active material (207, 307, 407, 507, 1107) forming a non-uniform distribution of said binding material and said active material in each of said units.

19. the active material imparts physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological properties, or combinations thereof, to the structure; and 20. The structure of claim 18, wherein said active material imparts electrical properties to said continuous structure, said electrical properties including electronic conductor, ionic conductor, semiconductor, electrical insulator, or combinations thereof.

20. 20. The structure of claim 18 or 19, wherein the active material is non-uniformly distributed within the area of ​​each microstructure unit bounded by the respective unit.

21. 21. The structure of any one or any combination of claims 18, 19, or 20, wherein the binding material comprises an organic material, an inorganic material, or a combination thereof.

22. A structure as claimed in any one or any combination of claims 18 to 21, wherein the uneven distribution of the binding material and the active material in each of the units comprises one or more of the following: a binding material collected at an end of said unit; a binding agent collected adjacent to a boundary formed by said binding agent; Each unit has a hollow center and contains no active or binding material, or Active material collected at the end of the unit.

23. 22. The structure of any one or any combination of claims 18 to 21, wherein the structure comprises a continuous planar layer (550, 1150) or a plurality of stacked planar layers (550, 1150).

24. The structure described in claim 23, wherein the structure includes a plurality of stacked planar layers, a first layer including the same active material as an active material of a second layer of the plurality of stacked layers, and the first layer having particle size characteristics different from the second layer of the plurality of stacked layers.

25. 25. The structure of any one or any combination of claims 18 to 24, wherein each microstructural unit comprises an area bounded by at least three sides, and a subset of the plurality of microstructural units comprises an area bounded by six sides to form honeycomb cells.

26. 26. The structure of any one or any combination of claims 18 to 25, wherein the active material intercalates lithium ions or has a conversion reaction in the presence of lithium ions.

27. 27. The structure of any one or any combination of claims 18 to 26, wherein the active material comprises one or more of the following: an active catalyst capable of effecting or promoting a chemical reaction between reactants, said reactants and products of said chemical reaction being passed through said microstructure unit; an active adsorbent capable of selectively binding to an adsorbate, and a medium carrying the adsorbate is passed through the microstructure unit; an active adsorbent capable of providing a response upon binding with an adsorbent, said response comprising a change in at least one of a physical, chemical, electrical, optical or magnetic property of said active adsorbent; an active carrier of a compound and capable of releasing at least a portion of said compound in a controlled manner upon contact with a transport medium, said transport medium being passed through said microstructure unit; an active carrier for a photosensitive compound, the photosensitive compound providing an optical response when excited by light; an active carrier of a magnetically sensitive compound, said magnetically sensitive compound providing a magnetic response when magnetically excited; or It is an active carrier for a pigment, which provides an optical response when the pigment is excited with visible, ultraviolet, or infrared light.

28. An article of manufacture comprising a structure according to any one or any combination of claims 18 to 27.

29. 30. The article of claim 28, wherein the article is an electrochemical cell, and the electrochemical cell comprises an electrode, a cathode, an anode, a separator, a solid electrolyte, or a semi-solid electrolyte comprising the structure.

30. 30. The article of any one or any combination of claims 28 or 29, wherein the support is comprised in a cathode, an anode, a separator, a solid electrolyte, or a semi-solid electrolyte.

31. 1. A composition comprising a flowable liquid comprising a homogenous mixture of an active material (207, 307, 407, 507, 1107) and a binding material (209, 309, 409, 509, 1109), wherein when droplets (103, 203, 303) of the composition are deposited on a support, the droplets self-assemble to form a continuous structure (330, 530, 1130), the continuous structure comprising a plurality of microstructure units (105, 205, 305, 405), the binding material and the active material self-segregating to form a non-uniform distribution of material in each of the units.

32. the active material imparts physical, thermal, chemical, catalytic, electrical, magnetic, radioactive, photonic, biological properties, or combinations thereof, to the continuous structure; and 32. The composition of claim 31, wherein the active material imparts electrical properties to the continuous structure, the electrical properties comprising an electronic conductor, an ionic conductor, a semiconductor, an electrical insulator, or a combination thereof.

33. 33. The composition of any one or any combination of claims 31 or 32, wherein the binding material comprises an organic material, an inorganic material, or a combination thereof, or the binding material comprises a liquid carrier comprising an inorganic composition or an organic composition.

34. 34. The composition of any one or any combination of claims 31 to 33, wherein the binding material self-segregates to collect at the ends of the unit.

35. 35. The composition of any one or any combination of claims 31 to 34, wherein the flowable liquid further comprises a substance adapted to alter the surface charge or zeta potential of at least one of the active material or the binding material, the substance comprising a coupling agent, a silane, a surfactant, a dispersant, or a combination thereof.

36. The composition of claim 31, wherein the flowable liquid has a viscosity of from 3 centipoise to 1500 centipoise, and the mass ratio between the active material and the binding material is from 0.000001 to 1,000,000.

37. Obtaining (1502) a flowable liquid containing a homogenous binding material (209, 309, 409, 509, 1109); generating (1504) a plurality of droplets (103, 203, 303) from the fluid liquid; and depositing 1506 the plurality of droplets onto a support; A method (1500) for manufacturing a structure, in which a plurality of droplets self-assemble to form a continuous structure (1230), the continuous structure comprising a plurality of microstructure units (1205), and a binding substance self-segregates to form a non-uniform distribution of the binding substance in each unit.

38. A structure (1230) comprising a plurality of microstructure units (1205), each of said units comprising self-segregated binding substances (209, 309, 409, 509, 1109) so as to form a non-uniform distribution of binding substances in each of said units.

39. An article of manufacture comprising the structure of claim 38, further comprising a support comprising a polymeric film coated by the structure.